Redistributing load using wearable resistance during power clean training improves athletic performance - Marriner, C. R.; Cronin, J. B.; Macadam , P.; Storey, A. (European Journal of Sport Science, 2017)
A popular method to improve athletic performance and lower body power is to train with wearable resistance (WR), for example, weighted vests. However, it is currently unknown what training effect this loading method has on full-body explosive movements such as the power clean. The purpose of this study was to determine what effects WR equivalent to 12% body mass (BM) had on the power clean and countermovement jump (CMJ) performance. Sixteen male subjects (age: 23.2 ± 2.7 years; BM: 90.5 ± 10.3 kg) were randomly assigned to five weeks of traditional (TR) power clean training or training with 12% BM redistributed from the bar to the body using WR. Variables of interest included pre and post CMJ height, power clean one repetition maximum (1RM), peak ground reaction force, power output (PO), and several bar path kinematic variables across loads at 50%, 70%, and 90% of 1RM. The main findings were that WR training: (1) increased CMJ height (8.7%; ES = 0.53) and 1RM power clean (4.2%; ES = 0.2) as compared to the TR group (CMJ height = -1.4%; 1RM power clean = 1.8%); (2) increased PO across all 1RM loads (ES = 0.33-0.62); (3) increased barbell velocity at 90% 1RM (3.5%; ES = 0.74) as compared to the TR group (-4.3%); and (4) several bar path kinematic variables improved at 70% and 90% 1RM loads. WR power clean training with 12% BM can positively influence power clean ability and CMJ performance, as well as improve technique factors.